2017
DOI: 10.2319/090717-602.1
|View full text |Cite
|
Sign up to set email alerts
|

Lingual orthodontic treatment: A YouTube™ video analysis

Abstract: Objectives: The aim of this study was to examine the quality of information offered for patients seeking information on lingual orthodontic treatment. Materials and Methods: YouTubee was searched for videos about lingual orthodontic treatment using the key word ''lingual braces'' from the Google Trends application. One hundred and four videos were selected to be analyzed from the first 120 results. The video content was evaluated using a 10-point score, which was used for classifying low-and high-content video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
134
3
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(189 citation statements)
references
References 24 publications
31
134
3
21
Order By: Relevance
“…The findings about video source were similar to previous studies, which found that most medical videos were uploaded from patient sources. 10,21,22 In the current study, the rich-content versus poorcontent video group had higher GQS scores, and a moderate correlation was evident between GQS and content score. Similarly, Lena and Dindaroglu 10 also found a moderate correlation between quality and content in their YouTube analyses about lingual orthodontics.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…The findings about video source were similar to previous studies, which found that most medical videos were uploaded from patient sources. 10,21,22 In the current study, the rich-content versus poorcontent video group had higher GQS scores, and a moderate correlation was evident between GQS and content score. Similarly, Lena and Dindaroglu 10 also found a moderate correlation between quality and content in their YouTube analyses about lingual orthodontics.…”
Section: Discussionsupporting
confidence: 43%
“…Because YouTube provides audiovisual information, patients often preferred this medium to other social media platforms to seek health information. 9,10 The video characteristics of this study showed that YouTube users watched videos about Invisalign treatment at high rates, often uploaded videos, and frequently interacted with other users via comment, like, and dislike features. According to mean GQS score, the videos in this study were generally of moderate quality, whereas the mean reliability score showed that video reliability was generally poor.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our search was limited to first 50 videos for each keyword. It has previously been explained in multiple studies that most Internet users do not look beyond the first 50 search results 16,[28][29] For the search of videos in Mandarin, we used the Mandarin translation of 'Wuhan virus' and not '2019 Novel Coronavirus'. This strategy was based on our preliminary review of number of videos with each search term.…”
Section: Limitationsmentioning
confidence: 99%